Pathological Role of Fractalkine/CX3CL1 in Rheumatic Diseases: A Unique Chemokine with Multiple Functions - Jones, Brian (Frontiers Research Foundation, 2012)
Understanding rheumatic diseases from the perspective of chemokine biology has shaped and will continue to shape our approach for targeted drug design. Among different kinds of chemokines, fractalkine/CX3CL1 has been found to play an important role in inflammation, portraying unique functional, and structural characteristics. This review summarizes the emerging role of fractalkine/CX3CL1 from a functional and clinical perspective and provides evidence to validate it as a potential therapeutic target in rheumatic diseases such as rheumatoid arthritis, Sjögren’s syndrome, systemic lupus erythematosus, scleroderma, as well as diseases related to vascular inflammation. From this, recent studies investigating potential therapeutic agents against fractalkine/CX3CL1’s role in pathology have shown promise.